2010
DOI: 10.1111/j.1365-2109.2010.02554.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation with Bacillus subtilis on the growth, performance, immune response and antioxidant activities of the shrimp (Litopenaeus vannamei)

Abstract: The objective of this study was to evaluate the effect of dietary supplementation of a probiotic bacterium, Bacillus subtilis, on the growth, immune response and antioxidant activities of shrimp (Litopenaeus vannamei). Shrimps with an average initial weight of 2.11±0.17 g were randomly assigned to four groups with three replicates. The control group was fed a basal diet, and three treated groups were fed diets supplemented with B. subtilis at doses of 1 × 104, 5 × 104 and 10 × 104 colony‐forming unit (CFU) g−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
87
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(99 citation statements)
references
References 38 publications
(51 reference statements)
10
87
1
1
Order By: Relevance
“…These differences were found to be statistically significant (P<0.05). Similar improved survival has been reported in M. rosenbergii PL fed with L. sporogenes bioencapsulated diets [5], Binifit TM supplemented diets [6], Biogen® supplemented diets [8] and different probiotics supplemented diets [9], and in shrimps, fed with L. acidophilus, S. cremoris, L. bulgaricus-56 and L. bulgaricus-57 incorporated diets [21], B. subtilis incorporated diets [25] and Bacillus sp incorporated diets [26].…”
Section: Survival Performancesupporting
confidence: 54%
“…These differences were found to be statistically significant (P<0.05). Similar improved survival has been reported in M. rosenbergii PL fed with L. sporogenes bioencapsulated diets [5], Binifit TM supplemented diets [6], Biogen® supplemented diets [8] and different probiotics supplemented diets [9], and in shrimps, fed with L. acidophilus, S. cremoris, L. bulgaricus-56 and L. bulgaricus-57 incorporated diets [21], B. subtilis incorporated diets [25] and Bacillus sp incorporated diets [26].…”
Section: Survival Performancesupporting
confidence: 54%
“…Average daily growth (ADG) was high in S. cerevisiae (0.106±0.002 g) and B. subtilis (0.104 ± 0.002 g) followed by other strains such as Sb (0.092 ± 0.002 g), Lc (0.083 ± 0.001 g), Lr (0.082 ± 0.001 g), Ent (0.065 ± 0.004) and Cp (0.064 ± 0.002 g) whereas in control it was observed to be the lowest (0.062 ± 0.004 g). Similar to our findings, several studies have demonstrated the beneficial effects of probiotics on the growth performance in shrimp (Wang et al, 2007;Shen et al, 2010;Liu et al, 2009). …”
Section: Evaluation Of Probiotics In Penaeus Vannameisupporting
confidence: 92%
“…However, other organisms, such as fungi and yeasts, have also been used for probiotic purposes (Devajara et al, 2002;Ribeiro et al, 2008). Research on probiotics for aquatic animals is increasing with the demand for sustainable, environmentally friendly aquaculture (Wang et al, 2005;Farzanfar, 2006;Ravi et al, 2007;Decamp et al, 2008;Li et al, 2008;Gomez et al, 2009;Guo et al, 2009;Liu et al, 2009;Ninawe & Selvin, 2009;Peraza-Gómes et al, 2009;Pai et al, 2010;Shen et al, 2010;Silva et al, 2011Silva et al, , 2012Souza et al, 2011;Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%